Malignant Extra-Gastrointestinal Stromal Tumor of the Pancreas. A Case Report and Review of Literature - Vij, Mukul; Agrawal, Vinita; Pandey, Rakesh (JOP. Journal of the Pancreas, 2011)
Context Gastrointestinal stromal tumors are CD117 (C-Kit) positive mesenchymal neoplasms considered to originate from the interstitial cells of Cajal. Gastrointestinal stromal tumors have been described outside the gastrointestinal tract in sites, such as the mesentery, omentum and retroperitoneum; however, pancreatic extra-gastrointestinal stromal tumors are extremely rare and there have only been seven previous reports in the literature. Case report We describe a 38-year-old man with a malignant pancreatic gastrointestinal stromal tumor. The tumor was located in the head of pancreas, measured 6.5x5.0 cm and was well circumscribed. On histology, it showed a mixed spindle and epithelioid cell morphology with the presence of sheets and short intersecting fascicles of tumor cells. There was a mitotic count of 12-15 mitoses per 50 high-power fields. The differential diagnosis included a pancreatic smooth muscle tumor and a neuroendocrine tumor. Immunohistochemistry revealed diffuse cytoplasmic positivity for CD117 and vimentin. Tumor cells were negative for CD34, S100, desmin, smooth muscle actin (SMA), cytokeratin, neuron specific enolase, chromogranin and synaptophysin. The patient developed isolated liver metastasis two years after the resection of the primary tumor. The resected metastasis showed a similar tumor. The patient was treated with imatinib mesylate and the post-operative course two years after resection of the liver metastasis has been uneventful. Conclusion We report a rare case of pancreatic gastrointestinal stromal tumor presenting as a solid neoplasm and review the cases previously described in the literature. Image: Metastatic tumor deposits in the liver parenchyma with strong CD117 expression.